Use of Microorganisms in the Recovery of Oil From Recalcitrant Oil Reservoirs: Current State of Knowledge, Technological Advances and Future Perspectives - Nikolova, Christina; Gutierrez, Tony (Frontiers in Microbiology, 2020)
The depletion of oil resources, increasing global energy demand, the current low, yet unpredictable, price of oil, and increasing maturity of major oil fields has driven the need for the development of oil recovery technologies that are less costly and, where possible, environmentally compatible. Using current technologies, between 20 and 40% of the original oil in a reservoir can be extracted by conventional production operations (e.g. vertical drilling), with secondary recovery methods yielding a further 15-25%. Hence, up to 55% of the original oil can remain unrecovered in a reservoir. Enhanced oil recovery (EOR) is a tertiary recovery process that involves application of different thermal, chemical, and microbial processes to recover an additional 7-15% of the original oil in place (OOIP) at an economically feasible production rate from poor-performing and depleted oil wells. EOR can significantly impact oil production, as increase in the recovery rate of oil by even a small margin could bring significant revenues without developing unconventional resources. Microbial enhanced oil recovery (MEOR) is an attractive, alternative oil recovery approach, which is claimed to potentially recover up to 50% of residual oil. The in-situ production of biological surface-active compounds (e.g. biosurfactants) during the MEOR process does not require vast energy inputs and are not affected by global crude oil prices. Compared to other EOR methods, MEOR can be an economically and more environmentally friendly alternative. In this review, the current state of knowledge of MEOR, with insights from discussions with the industry and other stakeholders, is presented and in addition to the future outlook for this technology.